Implementasi Pengolahan Kotoran Sapi Menjadi Kompos Menggunakan EM4 di Desa Namotongan, Kabupaten Langkat - Muslim Lubis; Dio Arif Hanafi Harianja; Tasya Ika Saylani Tarigan; Natasya Natasya (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
Cow manure in Namotongan Village has not been optimally utilized, creating environmental pollution risks. This community service program aimed to provide training on compost production using Effective Microorganisms (EM4) for livestock waste utilization. The program applied a Participatory Action Research (PAR) design, involving 30 participants consisting of farmers, livestock breeders, and local youth. Activities included preparation, socialization, hands-on practice, mentoring, and evaluation. Evaluation used a Likert-scale questionnaire (1–5, 15 items) and compost quality tests based on final temperature (°C), moisture content (%), pH, C/N ratio, color descriptors, and odor assessed by a subjective calibrated scale. Results indicated an increase in mean knowledge scores from 62% to 88% and skills from 58% to 85% (p < 0.05). A total of 80% of participants agreed that the material was relevant, while 75% found the practice easy to implement. The produced compost met quality standards with stable final temperature (31°C), appropriate moisture content, optimal pH, and C/N ratio of 23:1. The training effectively enhanced participants' capacity in livestock waste management and produced quality compost, although economic potential requires further study.